Optimization of corrosion resistance of AZ31 Mg alloy through hydration-driven interaction between quinolin-8-ol and plasma electrolytic oxidation-formed MgO layer - Mosab Kaseem; Talitha Tara Thanaa; Ananda Repycha Safira; Alireza Askari; Arash Fattah-alhosseini (Journal of Magnesium and Alloys)
This study presents a novel approach to improving the anticorrosive performance of AZ31 Mg alloy by exploiting the role of the hydration reaction to induce interactions between Quinolin-8-ol (8HQ) molecules and the porous MgO layer formed via plasma electrolytic oxidation (PEO). The AZ31 Mg alloy, initially coated with a PEO layer, underwent a dipping treatment in an ethanolic solution of 0.05 M 8HQ at 50 °C for 3 h. The results were compared with those from a different procedure where the PEO layer was subjected to a hydration reaction for 2 h at 90 °C before immersion in the 8HQ solution under the same conditions. The hydration treatment played a crucial role by converting MgO to Mg(OH)₂, significantly enhancing the surface reactivity. This transformation introduced hydroxyl groups (−OH) on the surface, which facilitated donor-acceptor interactions with the electron-accepting sites on 8HQ molecules. The calculated binding energy (Ebinding) from DFT indicated that the interaction energy of 8HQ with Mg(OH)₂ was lower compared to 8HQ with MgO, suggesting easier adsorption of 8HQ molecules on the hydrated surface. This, combined with the increased number of active sites and enhanced surface area, allowed for extensive surface coverage by 8HQ, leading to the formation of a stable, flake-like protective layer that sealed the majority of pores on the PEO layer. DFT calculations further suggested that the hydration treatment provided multiple active sites, enabling effective contact with 8HQ and rapid electron transfer, creating ideal conditions for charge-transfer-induced physical and chemical bonding. This study shows that hydration and 8HQ treatments significantly enhance the corrosion resistance of Mg alloys, highlighting their potential for advanced anticorrosive coatings.